Thermal conductivity and air-mediated losses in periodic porous silicon membranes at high temperatures - B. Graczykowski (Nature Portfolio, 2017)
Nanostructuring of silicon allows acoustic phonon engineering, but the mechanism of related thermal transport in these structures is not fully understood. Here, the authors study the heat dissipation in silicon membranes with periodic nanoholes and show the importance of incoherent scattering.